Botanical illustration from Chelsea Physic Garden - Brown, Andrew 1948-; Bailes, Christopher; Cribb, Philip J. 1946-; Evans, Anne-Marie (Antique Collectors' Club, 2015)
Chelsea Physic Garden was founded by the Worshipful Society of Apothecaries in 1673 as a resource providing plant material for the training of apothecaries. For most of its existence, the Garden has been a focus for botanists, taxonomists, students and horticulturists both for employing their skills and in training the next generation. These activities have been supported by the work of plant illustrators. It is the purpose of this book to display the work of talented late twentieth- and early twenty-first century botanical artists, members of Chelsea Physic Garden Florilegium Society, whose explicit aim is to illustrate plants in cultivation in the Garden